The Influence of Campus Environment on the Development of Self-Identity of Adolescent Students - Dian Leila Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to analyze the influence of the campus environment on the development of self-identity in adolescent students. Adolescence is a crucial period in the formation of self-identity, and the campus environment as one of the main social contexts plays an important role in this process. This study uses a quantitative approach with a survey method involving 200 adolescent students at one of the state universities in Indonesia. Data were collected through a questionnaire that measured various aspects of the campus environment, including social interactions, extracurricular activities, academic support, and campus facilities, and how these factors contribute to the development of student self-identity. The results of the data analysis show that the campus environment has a significant influence on the development of student self-identity. Positive social interactions, participation in extracurricular activities, and adequate academic support have been shown to contribute significantly to increasing students' self-confidence, self-understanding, and sense of social connectedness. Adequate campus facilities also support the process of exploring self-identity by providing space for students to develop their interests and talents. However, this study also found that some students faced difficulties in adjusting to the new campus environment, especially those from less supportive socio-economic backgrounds.